Satellite altimetry results over Lake Vostok, central East Antarctica, from CryoSat-2 (Nov 2010 - Feb 2024) and ICESat-2 (Apr 2019 - Apr 2024) - Maria T Kappelsberger; Veit Helm; Johan Nilsson; Martin Horwath; Alex S Gardner (PANGAEA, 2025)
This dataset contains satellite altimetry results over Lake Vostok, central East Antarctica, at two different processing stages: (1) surface elevation measurements along the satellite track and (2) monthly gridded surface elevation changes. Results from the CryoSat-2 satellite radar altimetry mission from November 2010 to February 2024 are provided at both processing stages and for the two waveform retrackers AWI-ICENet1 (based on a deep convolutional neural network architecture) and OCOG10 (10% of the offset center of gravity (OCOG) amplitude). The generation of the stage (2) gridded data from the stage (1) OCOG10-retracked measurements involve an empirical correction for the effect of time-variable surface and volume scattering. Hence, the resulting stage (2) dataset is labeled OCOG10-cor. For this empirical correction, we apply a tailored scattering correction using epoch differences over time intervals of 6 years and search radii of 5 km. The results from the ICESat-2 satellite laser altimetry mission from April 2019 to April 2024 are provided only at the processing stage (2). As input to our processing, we use the CryoSat-2 Level-1B waveform product Baseline E provided by ESA and the ICESat-2 ATL06.006 land ice height product (version 6) provided by NASA National Snow and Ice Data Center.